A Phenotyping Platform to Characterize Healthy Individuals Across Four Stages of Life - The Enable Study - Brandl, Beate; Skurk, Thomas; Rennekamp, Rachel; Hannink, Anne; Kiesswetter, Eva; Freiherr, Jessica; Ihsen, Susanne; Roosen, Jutta; Klingenspor, Martin; Haller, Dirk; Krautwurst, Dietmar; Hofmann, Thomas; et al. (Frontiers in Nutrition, 2020)
Introduction: Nutritional habits and requirements are changing over the lifespan, but the dynamics of nutritional issues and the diet-health relationship in the major stages of the human life cycle are not sufficiently understood. A human phenotyping research platform for nutrition studies was established to recruit and phenotype defined population groups across vulnerable stages of life. The project is the backbone of the highly interdisciplinary enable competence cluster of nutrition research aiming to identify dietary determinants of a healthy life throughout the lifespan and to develop healthier and tasty convenience foods with high consumer acceptance. Methods: The phenotyping program included anthropometry, body composition analysis, assessment of energy metabolism, health and functional status, multisensory perception, metabolic phenotyping, lifestyle, sociodemography, chronobiology, and assessment of dietary intake including food preferences and aversions. Results: In total, 503 healthy volunteers at four defined phases of life including 3-5-year old children (n=44), adolescents and young adults aged 18-25 years (n=94), adults aged 40-65 years (“middle agers”, n=205), and older people aged 75-85 years (n=160) were recruited and phenotyped, resulting in a comprehensive database. Plasma, serum, buffy coat, urine, feces and saliva were collected and stored at -80°C. Significant differences in anthropometric and metabolic parameters between the 4 groups were found. Conclusions: The dataset will provide novel information on differences in diet-related parameters over the lifespan and is available for targeted analyses. We expect that this novel platform approach will have implications for the development of innovative food products tailored to promote healthy eating throughout life. Trial registration: DRKS, DRKS00009797. Registered on 20 January 2016, https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00009797